Królestwa klientelne w Brytanii w latach 54 p.n.e. - 43 n.e. - Pietruszka, Wojciech (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2018)
The author of the article poses the question of the existence of client kingdoms in Britain in the period 54 BC – 43 AD. Analyzing narrative, numismatic and archaeological sources, he is inclined to support the hypothesis about their existence, although he critically refers to attempts to date their origin to just after Caesar’s expedition to Britain (thus rejecting the identification of Commius with the first client king, although he does not deny that Mandubracius could have been such a king as early as 54 BC) and links their (probable) beginning with the reigns of Augustus and Tincomarus (from the Southern Kingdom) and Tasciovanus (from the Eastern Kingdom).
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne